Enrich Schematization in Children: Play as The Tool for Cognitive Development - Vidya Bhagat, Mainul Haque, Kamarudin Jaalam (Journal of Applied Pharmaceutical Science, 2018)
Cognitive development gets toned by the improved external environment that can facilitate developing children. The play basing Piagetian cognitive development found to be a useful tool in enriching cognitive development in children. Parents and teachers can use naturalistic play therapy provided them with basic knowledge about Piagetian cognitive development and related play in the early stage of development. Thus, they can use their own pattern of play with age-related suitability that can enrich schemas in children and promote schematization process and cognitive development. The purpose of the article is to communicate newly created play therapy supporting cognitive development. Further to understand the role of play in Piaget’s schematization process. This article is useful in conceptualizing the perspective of cognitive development and its association with an interactive play in enriching schemas in the early development of children.
Keywords: Schematization, Play, Cognitive Development.